Effect of biodiesel blended fuel on the performance and emission characteristics of diesel engines - a review - Zheng, Fangyuan; Cho, Haeng Muk; Xu, Changchun (Zielona Góra: Uniwersytet Zielonogórski)
The internal combustion engine plays a vital role in transportation, industry, and shipping. However, diesel as one of the main fuels for internal combustion engines, caused many environmental and human health problems. In order to solve the problems, more researchers have been committed to the research of alternative fuels.
Keywords: biodiesel; Diesel engine; fuel properties; engine performance; exhaust emission